Decolonising the Origins of the University: Fatima al-Fihri and the Islamic Foundations of Higher Education - Alwy Ahmed Mohamed; Zakki Afifi; Muhammad Rehan Sabir; Muhammad Ndow; Qudra Bezibweki; Abdul-Samiu Abass (COMPETITIVE: Journal of Education, 2026)
The legacy of Fatima al-Fihri and the founding of the University of al-Qarawiyyin in Fez, Morocco, in 859 CE are the main topics of this work, which uses a decolonial perspective to investigate the historical underpinnings of higher education. This research contends that the fundamental frameworks of higher education were established within the early Islamic civilisation centuries earlier, despite prevailing historical narratives that frequently ascribe the origins of the modern university to medieval European institutions. The socio-religious, intellectual, and economic circumstances that made it possible for Al-Qarawiyyin to become a hub of higher education are examined in this study using historical-analytical methods and qualitative library research. The study also examines Al-Qarawiyyin's institutional elements, such as its curriculum, teaching strategies, ijazah certification system, and waqf-based financing structure, to determine how well they align with the fundamentals of the contemporary university model. The study questions dominant Eurocentric and gender-exclusionary narratives in the history of education worldwide by emphasising Fatima al-Fihri's role as founder. It shows that women in early Islamic civilisation were institutional architects of knowledge creation as well as intellectual participants. In the end, by reaffirming the contributions of Islamic civilisation to university formation, this study supports continued initiatives to decolonise the historiography of higher education. It makes the case that creating a more inclusive and truthful global history of education requires acknowledging Al-Qarawiyyin's fundamental importance.